The Role of Place Identity in the Perception, Understanding, and Design of Built Environments - Bernardo, Fátima (2013)
The Role of Place Identity in the Perception, Understanding, and Design of Built Environments INTRODUCTION As a contribution to previous literature dealing with identity and the physical environment, this eBook offers a deep insight about the role played by place identity with regard to architecture and the city. A major interest resides in exploring from a multidisciplinary perspective, how place identity affects and is affected by the bonds established between people and their environments. Considering that place identity is a controversial issue that continues to generate passionate discussion and not little discrepancy, this eBook is as an attempt to contribute to this debate. The volume is aimed at a broad audience of practitioners, educators, and researchers that embraces: architects and landscape architects, town planners and urban designers, environmental psychologists and environmental sociologists, ecologists, semioticians, geographers, folklorists and philosophers interested in the environment.